Policy options for improving regional fertilizer markets in West Africa - Bumb, Balu L.; Johnson, Michael E.; Fuentes, Porfirio A. (International Food Policy Research Institute, 2011)
A primary motivation for this study is to identify a key set of policy options for improving fertilizer markets in West Africa (among Economic Community of West African States member countries) in ways that ultimately will help improve the efficiency of regional markets and lower the transaction costs and fiscal burdens of increasing fertilizer use in the region. Guided by the 2008 fertilizer crisis, many governments are tempted to impose fertilizer subsidies to reduce fertilizer prices. Yet, in an environment riddled with inefficiencies that contribute to the high costs of using fertilizers, the introduction of subsidies only adds more fiscal burden.To carry out the study, we undertook four country case studies to review the key constraints and bottlenecks along the fertilizer supply chain. The countries were Ghana, Mali, Nigeria, and Senegal, and the research included field visits in 2009 and 2010. The current paper is based on the country case study results, complemented by a literature review and analysis of secondary data sources.